2022
DOI: 10.7874/jao.2021.00479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Versus Synthetic Consonant and Vowel Stimuli on Cortical Auditory-Evoked Potential

Abstract: Background and Objectives: Natural and synthetic speech signals effectively stimulate cortical auditory evoked potential (CAEP). This study aimed to select the speech materials for CAEP and identify CAEP waveforms according to gender of speaker (GS) and gender of listener (GL). Subjects and Methods: Two experiments including a comparison of natural and synthetic stimuli and CAEP measurement were performed of 21 young announcers and 40 young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…For specifics on other electrodes, please refer to the details in https://osf.io/wcemb/. The results are consistent with Manfredi et al (2021)'s andSong et al (2022)'s research, which suggests the asymmetry in frontal EEG activity is associated with experiential pleasure. Then, we analyzed four common waves (α, β, θ, δ) in human brain electrical activity in the prefrontal from both groups by using independent samples t-test, and the following results emerged:…”
Section: Phase 1 Eeg Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For specifics on other electrodes, please refer to the details in https://osf.io/wcemb/. The results are consistent with Manfredi et al (2021)'s andSong et al (2022)'s research, which suggests the asymmetry in frontal EEG activity is associated with experiential pleasure. Then, we analyzed four common waves (α, β, θ, δ) in human brain electrical activity in the prefrontal from both groups by using independent samples t-test, and the following results emerged:…”
Section: Phase 1 Eeg Resultssupporting
confidence: 87%
“…We discovered that in the Chinese context, the human voice broadcast had a stronger mediating effect than the AIgenerated voice. This finding may be related to the fact that the Chinese language has more syllable, intonation, and stress variation than English, which leads to more cognitive scheduling and memory processing in the listener's brain and supports the Song et al's (2022) experiment, which suggested that the human voice and the synthetic voice processed different phonemes in the English context, resulting in different N2 and P3. In summary, hypothesis 2 was supported.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation